Development and validation of the organizational health behavior index: a mixed-methods instrument for measuring organizational health - Alzuman, Abad; Jaafari, Muath Al; Ali, Zaiba; Ali, Rahila; Bakadam, Lina Ibrahim (Frontiers in Psychology, 2025)
BackgroundOrganizational health is crucial to promote employees’ well-being, sustainable performances, and long-term survival; existing tools are, however, frequently unidimensional and have been developed without consideration for the organizational context.PurposeThe purpose of this study was to construct and validate the Organizational Health Behavior Index (OHBI), a composite measure that includes quantitative and qualitative domains.MethodsA sequential mixed-methods design was used to survey 7,548 workers in various Saudi industries. Subscale A (quantitative) comprised awareness, appreciation, relations, engagement, and communication satisfaction, which were validated through EFA, CFA, and reliability. Subscale B (qualitative) included organizational culture, employee persona, and voice, which were analyzed for theme, interrater reliability, and expert triangulation.ResultsCFA revealed a good fit (CFI = 0.960, TLI = 0.950, RMSEA = 0.053) with factor loadings > 0.70 and reliability α ≥ 0.707. Criterion-related validity demonstrated strong correlations (r = 0.75–0.83) with an existing model. The second aim we accomplished was to enhance our results by measuring employee-induced cultural perceptions (Subscale B).ConclusionThe OHBI is a reliable multidimensional measure of organizational health, providing both theoretical and practical value. Future validation work in other contexts is suggested.